Conversion of curved assemblies into two dimensional sheets - Deshmukh, Gunvant; Krishnamoorthy, Kothandam (Nanoscale, 2019)
The design and preparation of organic two dimensional (O2D) sheets and their conversion to curved nanostructures is in its infancy. To convert a flat structure into a curved structure, the molecule must have multiple interaction possibilities and an in-built twist. The conjugated small molecule iso-Indigo (i-Indigo) comprises two phenyl rings that are twisted (the dihedral angle is 15 degrees) at the junction. The i-Indigo has been connected with moieties that impart hydrogen bonding and van der Waals interactions. Due to the presence of the cloud in i-Indigo, - interactions are also present in the molecule. While all three interactions are in operation, rings and toroids are formed. Upon addition of hydrogen bonding competing solvents, the rings and toroids unravel to form O2D sheets. Control molecules that don't have hydrogen bonding moieties and - interactions form random assemblies. Please note that the rings, toroids and O2D sheets are formed in a single solvent by simple dissolution, unlike previous approaches that involve multiple steps and solvents.